Comprehensive evaluation of turbot (Scophthalmus maximus) upper thermal tolerance and body weight based on GRA-TOPSIS analysis - Ma, Aijun; Tian, Mi; Wang, Xinan; Huang, Zhihui; Sun, Zhibin; Liu, Zhifeng; Yan, Pengfei; Gou, Donghui (Frontiers in Marine Science, 2025)
IntroductionIn the past, for the evaluation of multiple traits of selected varieties, variance analysis and new multiple range method analysis were generally used to make a single comparative analysis of economic traits among different varieties and traits, and qualitative text descriptions were then used to evaluate the advantages and disadvantages of the tested varieties. However, this method lacks quantitative analysis and comprehensive evaluation, and has a high level of human subjectivity.MethodsIn order to comprehensively evaluate the high temperature tolerance and fast growth performance of turbot (Scophthalmus maximus), the grey relational analysis (GRA) and the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) analysis of upper thermal tolerance (UTT) and body weight (BW) measurements were performed, respectively. Fifty two-trait combination breeding families including 25 UTT♂ × BW♀ families and 25 UTT♀ × BW♂ families were analyzed.ResultsThe GRA showed that the ranges of the equal relational grade and the weighted relational grade were 0.61984–0.94876 and 0.66391–0.94063, respectively. The relational gradation of the equal relational grade and the weighted relational grade of 25 UTT♂ × BW♀ families were higher than those of 25 UTT♀ × BW♂ families, except for UTT10♂ × BW10♀, UTT11♂ × BW11♀, and UTT17♂ × BW17♀ families. UTT23♂ × BW23♀ had the highest equal relational grade and weighted relational grade. TOPSIS analysis results showed that the range of Ci* of the 50 families was 0.066614–0.936093. The Ci* values of 25 UTT♂ × BW♀ families were higher than those of 25 UTT♀ × BW♂ families except for UTT10♂ × BW10♀, UTT11♂ × BW11♀, and UTT17♂ × BW17♀ families. The UTT23♂ × BW23♀ family had the highest Ci*.DiscussionIt was obvious that, using both the GRA and TOPSIS method, the comprehensive evaluation results of heat tolerance and weight traits in UTT♂ × BW♀ families were generally better than those of UTT♀ × BW♂ families. This showed that a breeding method involving an initial cultivation of a high temperature resistant male strain and fast growing female strain, followed by hybridization between the two strains, may be a strategy worthy of consideration.